Impact of contingent rewards and punishments on employee performance: the interplay of employee engagement [version 2; peer review: 2 approved] - Debika Layek; Navin Kumar Koodamara (F1000Research, 2024)
Background This paper investigated the connection between transactional leadership styles, contingent rewards, punishments, and employee performance while emphasizing employee engagement’s mediating role. Existing research has predominantly focused on isolated associations between contingent rewards, punishment, and employee performance, leaving gaps in the empirical exploration of these mediating mechanisms. To address this research gap, our study has introduced a conceptual framework to understand the multifaceted connection between contingent rewards, punishment, and their effects on employee performance, with a specific emphasis on the mediating function of employee engagement. Methods We involved 273 full-time non-clinical healthcare professionals employed in NABH-accredited hospitals in Jharkhand, India. A structured survey instrument was employed for data collection from the specific survey participants, with the investigation of the research hypotheses conducted through the application of partial least squares-structural equation modeling (PLS-SEM). Results Preliminary findings suggested that contingent rewards and punishment do not directly influence employee performance. Instead, our study highlighted the critical mediating role of employee engagement, particularly its dimensions of Vigor, absorption, and dedication. Conclusions This research has underscored rewards and punishments as essential tools for influencing employee behaviour, motivation, and performance. Employee engagement, as a multifaceted construct, not only benefits individual employees but also significantly impacts overall organizational performance and success.